RICKETS - Sotvoldiyeva Nilufar Xabibulla qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation:This article discusses rickets, a childhood bone disease primarily caused by vitamin D deficiency, which leads to soft and weak bones. The article outlines the main causes, including lack of sunlight, poor nutrition, and certain medical conditions that affect nutrient absorption. It also highlights the common symptoms such as delayed growth, skeletal deformities, and muscle weakness. Diagnosis methods like blood tests and X-rays are described, along with effective strategies for prevention through sunlight exposure, balanced diet, and supplementation. The article concludes by emphasizing that rickets is both preventable and treatable with proper care and nutrition.